Avaliação do equilíbrio e atividade muscular de amputados de membro inferior protetizados - Pereira, Cinthia Herminia Carvalho Nascimento [UNIFESP] (2020)
Lower limb´s amputation causes physiological and biomechanical changes, with consequences for gait and balance, and deficit in balance is the most common limitation, increasing the risk of falls among amputees. The main objective of this study is to evaluate the dynamic balance and muscular activity, in the orthostatic posture, of prosthetic lower limb amputees, during functional reach. 12 healthy subjects participated in the control group and 10 amputated subjects in the experimental group. The individuals remained standing on the baropodometer and performed maximum forward and lateral reach, with three repetitions each. The distance reached was measured using a tape measure attached to the wall and the muscular activity of the posterior trunk region by surface electromyography. The lateral reaches were defined as reaching the dominant side and the non-dominant side. In amputees, the dominant side corresponded to the contralateral side to amputation, while in controls it was the limb side of preference for support. Significant differences were found in the stabilometric variables (length, average speed, speed X, deviation X, deviation Y in forward reach; deviation X in dominant side reach; speed Y and deviation X in non-dominant side reach), distance achieved, weight-bearing in the limbs and muscle activity between the groups. Amputees had a worse balance in the three types of reach, especially in the forward reach. They had even less distance achieved, higher values of muscle activation and preference for weight-bearing on the healthy limb. The rehabilitation time positively influenced the balance during the forward reach and non-dominant reach side. Muscle activity during all reaches was greater the longer the rehabilitation time. The weight-bearing on the prosthesis contributed to a better balance during the forward reach. This study establishes a basis for understanding the possible differences between amputees and healthy individuals. Larger samples with more homogeneous clinical characteristics should be investigated, as well as the influence of posterior trunk muscle activity on dynamic balance. The development of prosthetic components capable of providing sensory feedback can bring significant benefits.